2014
DOI: 10.1136/annrheumdis-2014-206456
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus versus mycophenolate mofetil for induction therapy of lupus nephritis: a randomised controlled trial and long-term follow-up

Abstract: Hospital Authority Research Ethics Committee Clinical Trial Registry (HARECCTR0500018; Hong Kong) and US ClinicalTrials.gov (NCT00371319).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(113 citation statements)
references
References 45 publications
4
100
0
4
Order By: Relevance
“…A multitarget approach is appealing as the pathogenesis of SLE involves several immune pathways. CNIs plus corticosteroids alone have also been used for LN induction and found to be as effective as MMF for proliferative LN (98). At this time, CNI studies need to be viewed cautiously.…”
Section: Other Emerging Therapiesmentioning
confidence: 99%
“…A multitarget approach is appealing as the pathogenesis of SLE involves several immune pathways. CNIs plus corticosteroids alone have also been used for LN induction and found to be as effective as MMF for proliferative LN (98). At this time, CNI studies need to be viewed cautiously.…”
Section: Other Emerging Therapiesmentioning
confidence: 99%
“…Full-texts of the remaining 10 articles were retrieved for further review. Among them, 2 studies compared tacrolimus with placebo (Miyasaka et al 2009) or MMF (Mok et al 2010), and 3 studies (Bao et al 2007;Bao et al 2008;Bao et al 2009) compared tacrolimus plus MMF with IVCYC were excluded. At last, 5 eligibility citations (Zhang et al 2006a;Zhang et al 2006b;Xu et al 2007;Chen et al 2011;Li et al 2011), including 2 in English and 3 in Chinese, were included in the metaanalysis.…”
Section: Study Selectionmentioning
confidence: 99%
“…Mok et al [59] reported the outcomes of patients with class III/IV/V LN given corticosteroids and TAC as induction therapy followed by low-dose corticosteroids and AZA maintenance, and the complete remission rate at 6 months was comparable to that for patients treated with corticosteroids and MMF for induction followed by AZA during maintenance (59 vs. 62%; p = 0.71). The two groups showed similar rates of major infection (9.2 vs. 5.4%; p = 0.53) and cumulative incidence of renal failure at 5 years (21 vs. 22%; p = 0.35) [59]. The numerically higher rate of renal flares in the TAC induction group did not reach statistical significance, and there was no definite conclusion on the impact of TAC on the long-term evolution of renal function.…”
Section: Emerging Treatments In Asia and Concluding Remarksmentioning
confidence: 99%
“…We have reported our data on the efficacy of TAC when used as add-on therapy, guided by therapeutic drug level monitoring, in patients with LN who showed persistent significant proteinuria despite treatment with other immunosuppressive agents, and in patients given long-term TAC therapy the renal survival rate at 3, 5 and 8 years was 93, 83 and 83%, respectively [50]. Mok et al [59] reported the outcomes of patients with class III/IV/V LN given corticosteroids and TAC as induction therapy followed by low-dose corticosteroids and AZA maintenance, and the complete remission rate at 6 months was comparable to that for patients treated with corticosteroids and MMF for induction followed by AZA during maintenance (59 vs. 62%; p = 0.71). The two groups showed similar rates of major infection (9.2 vs. 5.4%; p = 0.53) and cumulative incidence of renal failure at 5 years (21 vs. 22%; p = 0.35) [59].…”
Section: Emerging Treatments In Asia and Concluding Remarksmentioning
confidence: 99%